Plio-Pleistocene Dust Traps on Paleokarst Surfaces: A Case Study From the Carpathian Basin - Kovács, János; Újvári, Gábor; Varga, György; Seelos, Klemens; Szabó, Péter; Dezső, József; Gammoudi, Nadia (Frontiers in Earth Science, 2020)
Plio-Pleistocene silt/clay-rich deposits and paleo-karst fissure sediments from sites of the northern and southern parts of the Carpathian Basin were investigated. These materials were supposed to be mixed during transport before being captured in karstified fissures. Evidence that the eolian fissure sediments of Plio-Pleistocene age in the older Triassic–Cretaceous limestones are derived from eolian silt and clay includes compositional and textural matches, especially decreasing grain-size trends observed downwards from the paleo-surface of the former landscape. Various environmental factors could be recognized by the statistical evaluation of grain-size distribution curves of fissure fillings sediments, such as the effects of eolian transport, parent rock type, weathering, and other sediment transport processes. Grain-size distribution curves with a single maximum in the silt size range are typical for the overlying siltstone debris, for the redeposited loess and red paleosol underlying the loess. Red clay fissure fillings yield bimodal grain-size distribution curves with maxima both in the clay and silt fractions. The research reported in this paper identifies for the first time the presence of eolian deposits in karst fissures of the Carpathian Basin and investigates the characteristics and origin.